Understanding Religion and Social Change in Ethiopia - Girma, M. author. aut Link
XXI, 219 p.
Keywords: Religiosity is one aspect without which Ethiopian society cannot be fully understood. This book aims to map out the terrain of the discourse in religion-social change nexus in Ethiopian using the notion of covenant as an interpretive tool.